Integration between the conventional and Islamic stock indices with the US stock market: evidence from cointegration analysis - Saiti, Buerhan (INSI Publications, 2014)
Background:A low correlation between returns of cross-border stock market indices allows investors to minimize portfolio risk through international diversification. Due to high comovement among conventional stock indices, international investors are looking for different cross-border or asset classes such as ethical and Shari‟ah-compliant investments to reap the benefits of diversification. Objective: This paper investigates the comovement of conventional and Islamic stock indices in the daily returns among conventional and Islamic stock indices in East Asia and selective Islamic countries through the application of cointegration analysis. Our study is focused on investigating the following empirical question: Are the Islamic stock indices less cointegrated with the US market compared to that of the conventional indices with the US? Results: Our findings based on several cointegration techniques tend to suggest: the stock indices of Islamic countries cointegrated with the US stock index is weaker compared to that of the non-Islamic countries. This observation is based on the number of cointegrating vectors in Islamic countries with the US being much less compared to the number of cointegrating vectors in the non-Islamic countries with the US. Conclusion:The evidence of less cointegration between the stock indices of Islamic countries (compared to non-Islamic countries) with the US stock index, indicates the possibility of potential gains through diversification of Islamic investment portfolios with the US market. Knowledge of financial cointegration among stock indices is important for portfolio diversification by international investors.